American snapshots - Graves, Kenneth 1942-2016; Payne, Mitchell 1944-1977 (Scrimshaw Press, 1977)
"Collection of pictures gathered by the authors during a two-year search in which they canvassed neighborhoods and knocked on people's doors, asking to see people's dusty albums and yellowing scrapbooks."--From jacket flap
Keywords: Photography, Instantaneous; Photography / United States; Photography; United States; Bildband